The Impact of Crisis and Economic Sanctions on the Russian Insurance Market - Pukała , Ryszard (Studia Oeconomica Posnaniensia, 2018)
The Russian insurance market is going through hard times as a consequence of economic disturbances experienced in the years 2007-2015 that were triggered by internal problems, decreased prices of raw materials on global markets, lack of infrastructural reforms as well as economic sanctions imposed by the US, the EU and a number of developed countries in reaction to Russia's aggressive policy towards Ukraine. The main objective of this study is to analyse the impact of the crisis and economic sanctions on the Russian insurance market in the years 2007-2015. A research hypothesis has been formulated, assuming that the Russian insurance market is undergoing quantitative and qualitative changes resulting from economic disturbances of the 2007-2015 period, brought about by the global financial crisis and economic sanctions resulting from Russia's aggressive geopolitical actions. As shown by the results of analyses, despite unfavourable conditions the Russian insurance market is relatively stable; furthermore, it is observing numerous quantitative and qualitative changes that result in reduced market concentration, increased capitalization of existing insurance companies that follow legislative amendments, mergers and takeovers as well as the aspiration of insurers and supervisory bodies to increase the security of insurance clients.